Sliding mode control design of wind power generation system based on permanent magnet synchronous generator - Nada Zine Laabidine; Afrae Errarhout; Chakib El Bakkali; Karim Mohammed; Badre Bossoufi (Institute of Advanced Engineering and Science, 2021)
This paper aims to implement a new contribution for sliding mode control (SMC) of permanent magnet synchronous generator (PMSG) for wind systems conversion with track the maximum power point tracking (MPPT) power. The SMC is a very popular approach due to its robustness in dealing with the non-linear electrical power systems. In this work, the application of the SMC control is by using the non lineare model of the PMSG. The objective of this work is to control stator active and stator reactive power, and the voltage-frequency for a better injection into the network. The results obtained show better robustness.